HEAVY METAL CONCENTRATIONS OF COPPER AND NICKEL IN PERI-URBAN VEGETABLE AGRO-ECOSYSTEM OF MULTAN, PAKISTAN - H. Afzal; M. Ali; A. Sajjad; F. Nawaz; S. Saeed (Journal of Animal and Plant Sciences, 2023)
Industrialization and urbanization are the major contributors of heavy metal accumulation in soil and vegetables grown under peri-urban agro-ecosystems in Pakistan where farmers usually mix sewage waste water with irrigation water. However, the heavy metal accumulation among different functional groups of insects (i.e. pollinators, pests and predators) largely remains unknown under peri-urban agro-ecosystems. Therefore current study was planned to evaluate the accumulation of copper and nickel heavy metals in insect pollinators, predators and pests on luffa gourd grown in three peri-urban areas of Multan i.e. Soraj Miani,,Vehari Chowk and Rangeelpur. Source of irrigation at Soraj Miani was industrial and household sewage water while it was only household sewage water at other two locations. From each of the location, samples of three insect groups (Apis dorsata, Chrysoperla carnea and Spodoptera litura) were collected along with samples of water, plant, and soil. These samples were analyzed using the atomic absorption spectrophotometer (AAS) in order to quantify the accumulation of copper and nickel heavy metals. It was found that residues of copper and nickel metals were present in samples of soil (0.75 Cu, 0.57 Ni μg/g), water (0.10 Cu, 0.14 Ni μg/g), plants (0.13 Cu, 0.19 Ni μg/g) and insect pest (0.15 Cu, 0.15 Ni μg/g) up to varying extent. Therefore, heavy metals can pose serious threat to ecosystem services of pollination and predation in per-urban agro-ecosystem. Future studies should further investigate the impact of heavy metals on other important pollinators and predators in sewage waste water irrigated agro-ecosystems
Keywords: ecosystem services; insect pests; pollinators; predators; vegetables